“Cleopatra a Gipsy”: Performing the Nomadic Subject in Shakespeare’s Alexandria, Rome and London - Elam, Keir (Memoria di Shakespeare. A Journal of Shakespearean Studies, 2018)
At the beginning of Antony and Cleopatra the Egyptian queen is referred to as a ‘gypsy’. This term had different negative meanings in early modern English, from nomad to Egyptian to whore. The epithet evokes, among other things, the persecution of ‘Egyptians’, or gypsies, in Tudor and Stuart England, as well as the anti-vagrancy legislation and literature. This paper explores the ‘Egyptian’ qualities attributed to Cleopatra, especially her supposed nomadism, both in Shakespeare’s tragedy and in cultural history. Keywords: Cleopatra, Gypsies, Vagrancy laws, Nomadism, Cultural history